PERSEPSI SISWA TERHADAP MAHASISWA PLP 2 DI SMA AL-IMAN ULU ALE - Firman; Syahrir L; Suardi Zain; Damayanti Trisnawati; Selviana Putri; Muh Hanafi (ITB AAS Indonesia Surakarta, 2026)
This study aims to describe students’ perceptions of PLP II student-teachers at SMA Al-Iman Ulu Ale. The School Field Introduction Program II (PLP II) is an advanced stage of PLP I designed to strengthen student-teachers’ academic teaching competence and subject-matter competence through various school-based activities, including curriculum analysis, learning strategies and evaluation, instructional material development, the use of information and communication technology, teaching practice, and assistance in teachers’ administrative tasks. This study employed a descriptive quantitative approach. The research instrument was a questionnaire consisting of 20 statements using a four-point Likert scale, covering pedagogical, social, personality, and learning impact aspects. The respondents were 33 students of SMAS Al-Iman Uluale. The data analysis showed that the mean score of students’ perceptions was 65.06 out of a maximum score of 80, with an achievement percentage of 81.33%, indicating a high category. These findings reveal that students had positive perceptions of PLP II student-teachers, particularly in their ability to deliver learning materials, build positive interaction, demonstrate good attitudes and personality, and contribute positively to students’ learning motivation and interest. Therefore, the implementation of PLP II at SMA Al-Iman Ulu Ale received positive responses from students and supported the learning process at school.